Islamic fasting-an effective strategy for prevention and control of obesity - Khattak, Muhammad Muzaffar Ali Khan (Asian Network for Scientific Information, 2002)
A balanced and energy-restricted diet, exercise and behavior modification are the usual approaches used for obesity. Islamic fasting, which has the components of energy restriction and behavior modification, could be a safe nutritional approach for the prevention and treatment of obesity. For this reason, the effect of Islamic Fasting, an abstention from Foods, fluids and sex from dawn to sunset, on food intake, body weight and blood chemistry was studied in ten healthy adult male human subjects. Foods and Fluids intake before and in the first and fourth week of Fasting were recorded. Body weight of the participants was noted before and at the last day of Fasting. Blood samples before, in the second and fourth week of Fasting and two weeks after Fasting were collected. The daily reduction in energy (Food intake) ranged from 200-1500 Kcal with an average value of 857 410 Kcal. During the four weeks of Fasting, loss in body weight ranged from 0.5-6.0 Kg with an average value of 3.21.7 Kg. There were no significant differences in glucose, total protein, triglyceride and total, HDL and LDL cholesterol in the blood samples collected before, during and after the Fasting. The data suggest that Islamic Fasting is nutritionally safe and could be used as an effective strategy for prevention and control of obesity.